2021
DOI: 10.1007/s12187-021-09846-9
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Life Satisfaction Throughout Childhood and Adolescence: Differences in Young People’s Evaluations According to Age and Gender

Abstract: The level of life satisfaction perceived during childhood and adolescence is an excellent indicator of healthy psychological emotional development. The main aim of this work is to study the levels of life satisfaction perceived by young people throughout their childhood and adolescence. To this end, an innovative retrospective approach is adopted that shows how the evolution of life satisfaction is perceived at different ages according to gender. The present study is based on a sample of 600 Spanish adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
5
19
0
Order By: Relevance
“…From the perspective of positive psychology, children's strong sides, which interact with each other, positively correlate Lithuanian students during the Covid-19 pandemic and adolescence. The present results highlight the importance of psychological/affective care in the pre-adolescent age (Aymerich et al, 2021).…”
supporting
confidence: 61%
“…From the perspective of positive psychology, children's strong sides, which interact with each other, positively correlate Lithuanian students during the Covid-19 pandemic and adolescence. The present results highlight the importance of psychological/affective care in the pre-adolescent age (Aymerich et al, 2021).…”
supporting
confidence: 61%
“…Some studies indicate that there are no differences in the levels of well-being associated with gender, while others state that in general are more likely to show lower levels of well-being and life satisfaction ( Atienza-González et al., 2020 ; Kaye-Tzadok et al., 2017 ). These differences have been shown to be more marked as adolescence progresses ( Aymerich et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these trends, it is perhaps surprising that evidence is mixed on whether life satisfaction shows an increasing, decreasing, or stable trend throughout adolescence. A declining-with-age trend is perhaps the dominant finding in the literature, and has been reported in early cross-sectional studies from Israel (Ullman & Tatar, 2001), South Korea (Park, 2005), Romania and Spain (Casas et al, 2013), and Germany (Goldbeck et al, 2007) and recent longitudinal studies from Spain (Aymerich et al, 2021;González-Carrasco et al, 2017, Hong Kong (Shek & Liang, 2018), and Algeria (Tiliouine et al, 2019). However, a cross-sectional study in the United States did not find a change in life satisfaction across grades 9-12 (Huebner et al, 2004).…”
mentioning
confidence: 95%
“…A longitudinal study from Hong Kong found that males experienced a faster decline in life satisfaction than females in adolescence (Shek & Liang, 2018). In contrast, it has been suggested that biological (e.g., hormonal influences) and sociocultural influences (e.g., gender standards, expectations and stereotypes) may lead to a greater emotional vulnerability and more rapid decline in life satisfaction among girls than boys (Aymerich et al, 2021; Goldbeck et al, 2007). Recent longitudinal studies of Spanish adolescents (Aymerich et al, 2021; González‐Carrasco et al, 2020) have found that females experience sharper decreases in life satisfaction throughout adolescence than males.…”
Section: Introductionmentioning
confidence: 99%